The impact of preparatory classes on future student performance: Competency assessment experiences of Hungarian students in Covasna County - Barabás, Andrea; Bacskai, Katinka (Central European Journal of Educational Research, 2025)
This study examines the impact of the introduction of the preparatory class (reception class) in Romania as an early educational intervention within the framework of school readiness and educational inequality theories. The analysis focuses on Hungarian-speaking students in Covasna County, specifically on the first cohort of fourth-grade students who had previously attended this educational stage. The research is based on a quantitative, full-sample design, including all 1,054 fourth-grade students enrolled in Hungarian-language education. The dataset combines questionnaire data with results from the 2016–2017 national competence assessments, providing a comprehensive overview of academic performance in reading, mathematics, and natural sciences. The study investigates the relationship between participation in the preparatory year, socio-economic background, and academic achievement. The findings reveal a statistically significant association between parental educational attainment, labour market status and student performance. The results indicate that students from families with higher levels of education and more stable employment are significantly more likely to achieve above-average results. This suggests that while the institutional framework is inclusive, family background remains a decisive factor in how effectively children can capitalize on this preparatory period. Furthermore, participation is clearly associated with higher academic outcomes: students who completed the preparatory year are significantly more likely to achieve better results across all three assessed competence domains compared to those who did not. Overall, the preparatory class contributes to reducing the risk of school failure, supporting a smoother transition from preschool to primary education, and lowering early school leaving risks. It provides an extended preparatory period that helps children adapt more effectively to a performance-oriented learning environment. The study highlights the effectiveness of this universal reform while noting that, despite its mandatory nature, it cannot entirely neutralize the reproduction of social inequalities. In conclusion, the preparatory class represents a significant educational policy reform that improves student outcomes and promotes equity, particularly in minority-language and socio-economically disadvantaged contexts.